Methodology of psychological adaptation of skilled 15-17-year-old footballers to training and competitive loads - Nazarenko, L. D.; Kovalenko, A. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to experimentally substantiate the effectiveness of the methodology of psychological adaptation of qualified football players to training and competitive loads.